Physico-thermal properties of kenaf fiber/high-density polyethylene/maleic anhydride compatibilized composites - Salleh, Fauzani Md; Hassan, Aziz; Yahya, Rosiyah; Mohd Isa, Muhammad Rafiq; Lafia-Araga, Ruth Anayimi (SAGE Publications, 2018)
Kenaf fiber/high-density polyethylene/maleic anhydride (MA)-compatibilized composites were melt mixed in a twin-screw extruder and molded using injection molding machine. Physicothermal properties of the composites were studied at different percentages of compatibilizer contents using various techniques. The addition of 8% compatibilizer into 8.5 and 17.5 wt% fiber content improved the adhesion and tensile strength by 14.5% and 13.6%, respectively. Compatibilized samples exhibited higher peak load and fracture energy on impact testing compared to the samples without maleic anhydride compatibilizer. The effect of the addition of maleic anhydride compatibilizer on peak load and fracture energy was observed to be at its highest at 8%. Differential scanning calorimetric measurements revealed that the melting enthalpy and degree of crystallinity of composites increased with increasing compatibilizer content up to 8% and then decreased at 12% compatibilizer content. Dynamic mechanical analysis showed that the storage modulus of composites was increased, but the loss modulus and tangent delta were decreased after the addition of compatibilizer. This indicates that compatibilized composites produced have improved toughness and reduced stiffness.